ID 127 – Small world characteristics of cortical connectivity in acute stroke. Issue 3 (March 2016) - Caliandro, P.; Vecchio, F.; Miraglia, F.; Iacovelli, C.; Della Marca, G.; Lacidogna, G.; Reale, G.; Di Giannantoni, N.; Padua, L.; Rossini, P.M.
Abstract : Objective: After cerebral ischemia, disruption and subsequent reorganization of functional connections occur both locally and remote to the lesion. Recently, brain complexity has been described using the graph theory, an elegant approach which depicts important properties of complex systems by quantifying topologies of network representations. We tested whether ischemic stroke may determine changes in smallworldness of cortical networks as measured by cortical sources of EEG. Methods: Graph characteristics of EEG of 30 consecutive stroke patients in acute stage (no more than 5 days after the event) were examined. Connectivity analysis was performed using eLORETA in both hemispheres. Results: Network rearrangements are mainly detected in delta, theta and alpha bands. Similar findings were observed in both hemispheres regardless the side of ischemic lesion: bilaterally decreased smallworldness in the delta band; similar modification observed in the theta band, but statistically significant only in left hemisphere stroke patients. Conclusions: After an acute stroke, brain cortex rearranges its network connections diffusely, in a frequency-dependent modality in order to face the new anatomical and functional condition. Modifications in distinct frequencies suggests that the network remodelling occurs with different modalities. Key message: Stroke-related brain network reorganization could reflect a not negligible adaptive process.